Peran Gronjong Wariti dalam Mewujudkan Pemberdayaan Masyarakat Desa Mejono: Sebuah Tinjauan Kualitatif - Nanda Alistasari; Adin Fadilah (Institut Agama Islam Negeri Ponorogo, 2023)
The tourist attraction in Mejono Village is the Gronjong Wariti Tourism, founded by the community in 2017. The existence of this tourist attraction cannot be separated from the role of residents who care about their environment, as well as being committed to inviting residents to make it happen. This research aims to determine the Gronjong Wariti tourist attraction in Mejono Village, Plemahan Subdistrict, Kediri Regency, and the role of the Gronjong Wariti tourist attraction in empowering the people of Mejono Village, Plemahan Subdistrict, Kediri Regency. This research uses a qualitative approach with a descriptive research type. The data collection procedures used were interviews, observation, and documentation. Data analysis is done by reducing data, presenting data, drawing conclusions, and verifying. Checking the validity of the data is carried out by extending observations, persistence of observations, and triangulation. The results of this research are as follows: (1) Gronjong Wariti is a water tourist attraction that utilizes river water flow. Based on the classification of tourist attractions, Gronjong Wariti Tourism is a tourist attraction and special interest attraction because it opens visits to the public who want to visit this tourist attraction. This place has a lot of entertainment, from amusement rides to stalls selling traditional market snacks to a karaoke place. (2) The Gronjong Wariti tourist attraction empowers the community because it involves all the people of Mejono Village, namely at least 75 families in the community around the river. The involvement of all the people of Mejono Village has an impact on realizing the goals of community empowerment, namely institutional improvement, business improvement, income improvement, environmental improvement, life improvement, and community improvement.